The effect of communication between superior and subordinate / Kartini Mat Rashid, Asri Salleh and Adlan Ahmad Bakri - Mat Rashid, Kartini; Salleh, Asri; Ahmad Bakri, Adlan (2012)
Communication refers to two-way process of reaching mutual understanding, in which participants not only exchange (encode-decode) information but also create and share meaning. Communication is better when both parties understand the messages and skills in communication important to create effective communication between both parties like listening, observing, speaking, questioning, analysing, and evaluating skill. The objectives of this study were to identify the effect of communication between superior and subordinate. The data were collected using questionnaires and interviews. Descriptive statistic procedures were employed to describe the level of communication. The correlation between the independent variables and dependent variables were tested at 0.05 significant level using Pearson Correlations. The finding of this study indicated that the level of communication for both bottom up and top down communication were moderate because sometimes communication could either turn to be both effective and ineffective.